Tax aggressiveness and Corporate Political Connectedness - Azizah, Nurifa Laksmitasari; Kurnia Patmasari, Eka (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The focus of this research is corporate tax aggressiveness with political relations. We observe 625 companies every year and find that companies with political connections and listed on the IDX are more aggressive in taxation. However, an independent t test shows that there is no significant distinction among corporates that have political connections and corporates that do not. Additionally, these findings suggest that businesses with political connections are more profitable than businesses without political connections. Companies with political connections have lower leverage compared to profitability. This researcrch has practical and theoretical consequences, also these are discussed thoroughly.